Effects of meliponiculture Tetragonula laeviceps on pollinator diversity and visitation rate and citrus productivity in West Java, Indonesia - MUHAMAD ALDI NURDIANSYAH; Muhammad Yusuf Abduh; Agus Dana Permana (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Nurdiansyah MA, Abduh MY, Permana AD. 2023. Effects of meliponiculture Tetragonula laeviceps on pollinator diversity and visitation rate and citrus productivity in West Java, Indonesia. Biodiversitas 24: 5757-5763. Citrus reticulata var. Rimau Gerga Lebong (RGL) is a prominent Indonesian citrus variety, yet its global productivity is facing challenges due to decreasing diversity in pollinators. This study aimed to bolster the productivity of C. reticulata var. RGL in Bandung by introducing Tetragonula laeviceps Smith 1857 (Hymenoptera: Apidae). Simultaneously, the study explored the influence of pollinator diversity, foraging behavior, and visitation rates and compared the results with open and wind pollination. Field investigations were conducted to observe the pollination activities of T. laeviceps and eight wild pollinator species, including Apis cerana Fabricius 1793, Ceratina cognata Smith 1879, Xylocopa confusa Pérez 1901, Xylocopa latipes Drury 1773, Vespa affinis Linnaeus 1764, Dolichoderus thoracicus Smith 1860, Papilio demoleus Linnaeus 1758, and Catopsilia pyrantel Linnaeus 1758. T. laeviceps exhibited the highest relative abundance (34.87%) and an average time spent of 72.11 seconds per flower. Visitation rates were highest during noon (10:00 to 13:00) at 0.31 pollinators/hour/flower, influenced by temperature, relative humidity, and light intensity. The phenological stages of C. reticulata var. RGL spanned 240 days. Fruit set, fruit weight, and estimated citrus productivity were significantly higher in T. laeviceps and open pollination compared to wind pollination. This study highlights the suitability of T. laeviceps as an effective pollinator for C. reticulata var. RGL. The findings have implications for the conservation and management of pollinator populations to ensure sustainable citrus production in the declining global diversity.